ORGANIZATION DEVELOPMENT INTERVENTIONS ON THE GENERAL MANAGERIAL SKILLS OF COMMERCIAL BANK EXECUTIVES: A CASE OF KENYA COMMERCIAL BANK LIMITED IN KENYA, EAST AFRICA - Gathungu, James M.; Corvera, Jennilyn C. (European Scientific Journal, ESJ, 2015)
This study aimed to determine the effect of organization development Interventions (ODI) on the general managerial skills of the Bank Executives at Kenya Commercial Bank Limited (KCB) in Kenya, East Africa. It utilized an analytical descriptive action type research. Ninety eight (98) executives of the bank were the research subjects who comprised senior managers from head office, branch managers, section heads and supervisors of the bank. Universal sampling was done in identifying research subjects. The study was based on the theory advanced by Kraut et al (1989) who theorized that managers to be effective, they must have a clear understanding of different skills that are important in managerial role. These skills enabled managers to effectively coordinate work, communicate expectations, delivery of feedback, job transitions, training and career development activities. Preassessment was conducted to assess the general managerial skills of the bank executives and diagnose problem. The instrument was administered to the ninety eight (98) subjects who are presently employed in KCB Nairobi Branches. The results of pre-assessments on general managerial skills were good as indicated by the factor average rating of (Î¼ 2.816) but could be improved. Implementation of the planned interventions was guided by the schedule of activities. Seventy seven executives of KCB participated to improve performance. Understanding change through other people’s eyes by Vicki Schneider was conducted to provide insight on what is the importance of change. After the implementation of organization interventions, observation over a period of six months was done. Post assessment evaluation on the general managerial skills was done in January and February 2010. The result of the study revealed that there was a significant increase of the mean score in the post assessment in all the eight factors of the general managerial skills. There was improvement after the intervention in the general managerial skills as indicated by the increased mean from (Î¼ 2.816) to (Î¼3.959). The organization development interventions implemented were successful in improving the managerial skills in KCB as reflected in the increase of the mean ratings after intervention. The obtained t-value in general managerial skills was 5.149, which was greater than the critical value of 1.960. This meant that the null hypothesis was rejected. The organization development interventions implemented were successful in improving the general managerial skills of bank executives. The Organization Development Interventions yields a significant positive change in all the general managerial skills of the Bank Executives.